Deficits in medial prefrontal cortex parvalbumin expression and distraction-dependent memory in rats and mice in the sub-chronic phencyclidine model for schizophrenia - Landreth, Katie R.; Juty, Jacob; Mansour, Neveen; Radu, Patricia; Fletcher, Jennifer; Benalla, Imane; Grayson, Ben; Petersen, Rasmus S.; Harte, Michael K.; Gigg, John (Frontiers in Cellular Neuroscience, 2025)
IntroductionCognitive impairments associated with schizophrenia (CIAS) include deficits in declarative memory. This is associated with an inability to maintain information in short-term memory when distracted, and increased sensitivity to proactive interference. These CIAS may partly result from decreased expression of parvalbumin (PV) in medial prefrontal cortex (mPFC) interneurons. The sub-chronic phencyclidine (scPCP) rodent is a widely used model for schizophrenia that recapitulates CIAS, including declarative memory, social cognition and mPFC PV deficits. Thus, distraction before the test phase in novel object recognition (NOR) produces robust declarative memory deficits in scPCP rats. Controlling for distraction in the single trial or continuous NOR paradigm (cNOR) protects memory recall, and multi-trial cNOR reveals increased sensitivity to proactive interference for object memory. Here, we sought to expand scPCP model cross-species validity by comparing these NOR/cNOR deficits across scPCP rats and mice. We then aimed to determine whether distraction-dependent deficits are conserved across object and social memory domains in scPCP mice, assessing sociability and social memory using automated mouse tracking to sub-classify social interaction behaviors.MethodsscPCP mice underwent cNOR testing over 11 trials, and the density of cellular PV expression in putative interneurons (PVIs) in the mPFC was determined. scPCP mice were additionally tested in the Three-Chamber Social Interaction (TCSI) task, investigating social preference and the sensitivity of social memory to distraction. Mouse movement was tracked with a deep-learning tool (DeepLabCut) to classify sniffing and rearing in the TCSI task.ResultDistraction-dependent NOR deficits were conserved across scPCP rats and mice, while the effects of proactive interference on cNOR testing were species-specific. TCSI testing showed that scPCP mice expressed diminished sociability overall and increased susceptibility to distraction for social memory, particularly for rearing behavior. There was a significant reduction in PVI density in the scPCP mouse mPFC.DiscussionThese results extend the cross-species validity of the scPCP model in rodents. scPCP-induced susceptibility to distraction in mice is broadly comparable to that observed in scPCP rats and is conserved across object and social memory domains. These behavioral effects correlate with scPCP-induced decreases in PV expression in both species, further implicating altered mPFC excitatory-inhibitory balance in CIAS induction.